Identification of guanfu base A hydrochloride phase I and phase II metabolites in rat bile by liquid chromatography mass spectrometry. - A Ji-Ye; WANG Guang-Ji; WU Min-Shu; LIU Jing-Han (Acta Pharmacologica Sinica, 2016)
AIM: To study metabolites of guanfu base A hydrochloride (GFA) in rat bile. METHODS: An analytical method was developed to identify guanfu base A and its metabolites by liquid chromatography mass spectrometry (LC-MS) and electrospray ionization tandem mass spectrum (MS-MS). Rat bile was collected after iv injection of GFA. Phase I metabolite was identified by comparison with authentic standard for their retention time, molecular ion peaks, fragment ions, and UV spectrums. In order to identified Phase II conjugates, the aglycones were identified after rat bile was treated with either glucuronidase or sulfatase firstly. Phase II conjugates were also separated and determined for their molecular ions by LC-MS, at last they were verified by identifying characteristic product ions or precursor ions by MS-MS. RESULTS: Phase I metabolite, guanfu base I (GFI), was identified in rat bile. After phase II conjugates were treated with glucuronidase or sulfatase, GFA and GFI occurred in chromatograms. Quasi molecular ions m/z 606 and 510 were separated and detected in rat bile. They were indicated to be GFA glucuronide and GFA sulfate, respectively. Furthermore, GFA glucuronide was confirmed to exist in rat bile by identifying two characteristic ions, m/z 177, [M+H]+ of glucuronic acid, and m/z 430, [M+H]+ of GFA, as product ions of m/z 606. CONCLUSION: Phase I metabolite GFI and phase II conjugates, GFA glucuronide and sulfate, GFI glucuronide and sulfate, were identified in rat bile.